2021
DOI: 10.33687/phytopath.010.01.3516
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Okra Varieties for Resistance to Okra Yellow Vein Mosaic Disease under Field Conditions

Abstract: Okra (Abelmoschus esculentus L.) can contract okra yellow vein mosaic disease (OYVMD) caused by Bhendi yellow vein mosaic virus (genus: Begomovirus and family: Geminiviridae), vectored by whitefly (Bemisia tabaci). This study was carried out to screen okra varieties for resistance to OYVMD and to determine the correlation of vector population with the severity of the disease. Six varieties namely, Tulsi, Durgah, Sabz Pari, Sarahariya, Ramaan Kirshna and Pooja were grown under field conditions at localities of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
1
0
0
Order By: Relevance
“…The disease was gradually increasing till the last assessment. Such trend has been observed in other vector transmitted plant viral diseases (Khoso et al, 2021). These results are accordance with Zhang et al (2008) who observed that first symptom of the disease can be appear 15 days after transplantation, which are related with longer period till the end of crop.…”
Section: The Vector Population In Different Tomato Varieties and Its ...supporting
confidence: 90%
“…The disease was gradually increasing till the last assessment. Such trend has been observed in other vector transmitted plant viral diseases (Khoso et al, 2021). These results are accordance with Zhang et al (2008) who observed that first symptom of the disease can be appear 15 days after transplantation, which are related with longer period till the end of crop.…”
Section: The Vector Population In Different Tomato Varieties and Its ...supporting
confidence: 90%